Pengaruh Model Contextual Teaching And Learning (Ctl) Dan Motivasi Belajar Terhadap Hasil Belajar Siswa Kelas X Pada Mata Pelajaran Ekonomi Di SMA Negeri 11 Sijunjung - Rizka, Yusfar Miftahur; Ronald, Jimi; Jolianis, Jolianis (Jurnal Horizon Pendidikan, 2023)
This study aims to analyze the influence of the Contextual Teaching and Learning (CTL) contoh and learning motivation on the learning outcomes of grade X students in economics subjects at SMA Negeri 11 Sijunjung. In this study, the research used is quantitative. This research was conducted at Sekolah Menengan Atas Negeri 11 Sijunjung with a population of 50 and a sample of 50 students consisting of 25 experimental class students and 25 control class students. For thisresearch instrument carried out is through the distribution of questionnaires and questions. The data analysis techniques used are validity test, reliability test, difficulty level, differentiating power, normality test, homogeneity test and two-track Anova test with the help of SPSS acara version 18.0 The results showed: First, the learning outcomes of Economics students taught with the CTL method were higher than students taught with conventional learning methods Alaihi Salam seen from the value of t count lima,467 greater than t table 2.068, this means that thevalue of tcount is greater than ttable hence thus Accepted rejected. Second, the learning outcomes of Economics students with high Learning Motivation taught with the e CTL method are higher than the learning outcomes of Economics with high Learning Motivation taught with conventional learning methods AS seen from thecalculatedt value of 3.777 greater than the table t of 2.200, this means that thecalculated t value is greater than thetable t value thus Accepted rejected. Third, the learning outcomes of Economics students with low Learning Motivation taught with meto de CTL are higher than the learning outcomes of Economics with low Learning Motivation taught with conventional learning methods seen from the calculated t value of 5.857, this means that thecalculated t value is greater than thetable t value of 2.228, thus , Accepted rejected Fourth, there is an interaction between the CTL method and conventional learning methods with learning motivation on student learning outcomes AS seen from the value of the sig level. = 0.027, this means that the value of sig. is greater than the value of a = 0.05 (sig. < a) then thus rejected Accepted.Keywords : CTL Model,Learning Motivation,Learning Outcomes